FRAUD PADA SEKTOR PEMERINTAH BERDASARKAN FAKTOR KEADILAN KOMPENSASI, SISTEM PENGENDALIAN INTERNAL, DAN ETIKA ORGANISASI PEMERINTAH (Studi Empiris Dinas Pemerintah Provinsi DKI Jakarta) - Sulastri Sulastri (Jurnal Magister Akuntansi Trisakti, 2014)
This study discusses the fraud in the government sector especially Provincial Government of DKI Jakarta by three factors, there are the fairness of compensation, internal control systems, and organization of government ethics. In addition to discussing the factors that influence the occurrence of fraud in the public sector, this study also discusses appropriate strategies in response to the fraud problem. The population in this study is the Province Government of DKI Jakarta, while the sample is Office of the Province Government of DKI Jakarta. Sampling technique with Proportionate Stratified Random Sampling and hypothesis testing using SPSS. The data used in this study is primary data, through questionnaires distributed to civil servants working in the Office of the Province Government of DKI Jakarta. The results showed that there is an influence of all three factors, namely fairness of compensation, internal control systems, and organization of government ethics to fraud in the public sector when tested simultaneously. Where as if partially tested, only the fairness of compensation and internal control systems that have an impact on fraud, while organization of government ethics not. The research recommends to overcome fraud all problems with develop combined strategy of repressive and preventive for every level of organization, to provide effective compensation, and to implement good governance in the organization.